Comparison of QuantiFERON-TB Gold test and tuberculin skin test for the identification of latent Mycobacterium tuberculosis infection in lupus patients - DİRESKENELİ, RAFİ HANER; KARAKURT, SAİT (SAGE PUBLICATIONS LTD, 2012)
The tuberculin skin test (TST) has low sensitivity for the diagnosis of tuberculosis (TB). QuantiFERON-TB Gold (QFT-G) is an IFN-gamma-release assay that measures the release of interferon-gamma after stimulation in vitro by Mycobacterium tuberculosis antigens using ELISA. The main advantage of this assay compared with TST is the lack of cross-reaction with Bacillus Calmette-Guerin (BCG) as well as most of non-tuberculous mycobacteria. The aim of our study is to compare QFT-G with TST for the detection of latent tuberculosis infection (LTBI) among patients with systemic lupus erythematosus (SLE). Methods: Seventy-eight patients with SLE and 49 healthy subjects (HCs) participated in the study. All patients and controls were interviewed for a history of TB then BCG vaccinations were recorded and chest X-rays were examined for a sign of TB infection. QTF-G and TST were performed on both patients and controls. QTF-G results were recorded as positive, negative or indeterminate. A positive TST for SLE was defined as >= 5 mm. Results: Seventy-six SLE patients (97.4%) had been BCG vaccinated. Similar to the HC (28.5%), 19 of 78 (24.3%) SLE patients had positive QTF-G. Two patients had an indeterminate result. The agreement between QTF-G and TST was 49/76 (64.4%) (kappa = 0.33). There were fewer positive QFT-G test results than positive TST results (24.3% vs. 50%; p < 0.01). Twenty-two (28.9%) patients were TST(+)/ QTF-G(-) while only 3(3.9%) patients were TST(-)/ QTF-G(+). When the positive TST was defined as >= 10mm indurations, which is the cut-off in screening for LTBI in Turkey, the agreement between two tests increased up to 58/76 (76.3%) with a k value of 0.47. The mean TST measurements was higher in QTF-G positive patients (13.4 +/- 8.8 mm) than the QTF-G negative patients (4 +/- 5.3 mm) (p < 0.001). Discussion: In a TB-endemic and BCG vaccinated population, the QuantiFERON-TB Gold assay seemed to be a more accurate test for the detection of LTBI in SLE patients. Although 5mm is usually accepted to be the standard cut-off for TST in immunocompromised patients such as SLE, the level of agreement between QTF-G and TST was better with a 10mm cut-off in our population. Lupus (2012) 21, 491-495.
Keywords: Quantiferon-TB; latent tuberculosis; lupus; INTERFERON-GAMMA ASSAY; RHEUMATOID-ARTHRITIS; DIAGNOSIS